2015
DOI: 10.1039/c5ob00659g
|View full text |Cite
|
Sign up to set email alerts
|

Corrole and nucleophilic aromatic substitution are not incompatible: a novel route to 2,3-difunctionalized copper corrolates

Abstract: The insertion of a –NO2 group onto the corrole framework represents a key step for subsequent synthetic manipulation of the macrocycle based on the chemical versatility of such a functionality. Here we report results on the investigation of a copper 3-NO2-triarylcorrolate in nucleophilic aromatic substitution reactions with “active” methylene carbanions, namely diethyl malonate and diethyl 2-chloromalonate. Although similar reactions on nitroporphyrins afford chlorin derivatives, nucleophilic attack on carbon-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Paolesse and Smith groups found that corroles participate in S N Ar reactions at free β-positions of the macrocycle if appropriate β-substituents are attached to nearest positions . The NO 2 group is a very useful substituent in organic synthesis and it has been widely used in the functionalization of porphyrins .…”
Section: Post-functionalization Of Corrolesmentioning
confidence: 99%
See 2 more Smart Citations
“…Paolesse and Smith groups found that corroles participate in S N Ar reactions at free β-positions of the macrocycle if appropriate β-substituents are attached to nearest positions . The NO 2 group is a very useful substituent in organic synthesis and it has been widely used in the functionalization of porphyrins .…”
Section: Post-functionalization Of Corrolesmentioning
confidence: 99%
“…Paolesse and Smith groups found that corroles participate in S N Ar reactions at free β-positions of the macrocycle if appropriate β-substituents are attached to nearest positions. 327 The NO 2 group is a very useful substituent in organic synthesis and it has been widely used in the functionalization of porphyrins. 284 While it is well documented that β-nitroporphyrins can undergo nucleophilic addition and substitution reactions, only a few publications can be found on the functionalization of β-nitrocorroles, especially by S N Ar procedures.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they can react with nitrocorrole derivatives to afford VNS and ONSH reactions in the nitropyrrolic fragments. 54 As discussed above, chloro(nitroaryl)acetates produced in the VNS reaction of alkyl dichloroacetates upon hydrolysis and decarboxylation give (chloromethyl)nitroarenes. On the other hand, one-pot VNS reaction of alkyl dichloroacetate with nitroarenes and subsequent reaction with Michael acceptors results in the formation of alkyl (nitroaryl)cyclopropanecarboxylates (Scheme 21).…”
Section: Review Synthesismentioning
confidence: 96%
“…The electrophilicity of the C 2 ‐position has also been examined with C‐based active methylene nucleophiles. [ 227 ] Treatment of 162 with diethyl malonate and NaOH yielded the diester appended corrole 166 in 34 %. Reaction of 162 with diethyl chloromalonate gave a mixture of compounds, but only yielded 166 in 28 %.…”
Section: Snar Reactions Of Corrolesmentioning
confidence: 99%